RISK MANAGEMENT IN MINIMIZING KPR FINANCING RISK AT BANK BTN SYARIAH KCP PROBOLINGGO - Nasrifah, Maula (Finance : Journal of Accounting and Finance, 2023)
Bank BTN Syariah is one of the Islamic financial institutions that offers services in storing public funds and providing financing to customers in need, particularly through home ownership financing (KPR). As a sharia-compliant bank, BTN Syariah must carefully assess the eligibility of prospective debtors before approving financing applications. This assessment serves as a preventive measure to minimize potential risks or losses arising from non-performing financing (NPF). To manage these risks, BTN Syariah implements the 5C principle in its creditworthiness evaluation process, which includes Character, Capacity, Capital, Collateral, and economic Conditions. Furthermore, the bank employs several mitigation strategies such as implementing grace periods, rescheduling of principal balances, and restructuring outstanding financing obligations. This study seeks to explore how BTN Syariah applies risk management strategies specifically to its KPR products to reduce the occurrence of problematic financing. A qualitative descriptive method is used, combining literature review with field research through observation, interviews, and documentation. The findings reveal that KPR financing at BTN Syariah is prone to risks primarily stemming from the inability of debtors to fulfill their repayment obligations. This condition necessitates the presence of an effective risk management system that is responsive, preventive, and adaptive to ensure the bank’s financial stability while upholding sharia principles.